2014
DOI: 10.1002/pbc.24964
|View full text |Cite
|
Sign up to set email alerts
|

Neurological findings and genetic alterations in patients with Kostmann syndrome and HAX1 mutations

Abstract: SCN with HAX1 mutations, is a rare sub type of congenital neutropenia, mostly observed in population from Sweden and Asia minor, associating frequently neurological retardation, when the mutations involved the B isoform of the protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Almost all organs can present a dysfunction. Extra‐haematopoietic involvement may have a very strong impact on CN patients’ lives, such as the neurodevelopmental disorders observed in Kostmann syndrome (Roques et al , ), Shwachman‐Diamond syndrome (Kerr et al , ), and Cohen disease (Kivitie‐Kallio et al , ). Cardiac dysfunction may be very severe in Shwachman‐Diamond syndrome (Hauet et al , ) and WHIM syndrome (Badolato et al , ), and is almost always observed in Barth syndrome, leading to early death (Rigaud et al , ).…”
Section: The Phenotypes Of Congenital Neutropenia and Natural Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all organs can present a dysfunction. Extra‐haematopoietic involvement may have a very strong impact on CN patients’ lives, such as the neurodevelopmental disorders observed in Kostmann syndrome (Roques et al , ), Shwachman‐Diamond syndrome (Kerr et al , ), and Cohen disease (Kivitie‐Kallio et al , ). Cardiac dysfunction may be very severe in Shwachman‐Diamond syndrome (Hauet et al , ) and WHIM syndrome (Badolato et al , ), and is almost always observed in Barth syndrome, leading to early death (Rigaud et al , ).…”
Section: The Phenotypes Of Congenital Neutropenia and Natural Historymentioning
confidence: 99%
“…Almost all organs can present a dysfunction. Extra-haematopoietic involvement may have a very strong impact on CN patients' lives, such as the neurodevelopmental disorders observed in Kostmann syndrome(Roques et al, 2014), Shwachman-Diamond syndrome(Kerr et al, 2010), and Cohen disease (Kivitie-KallioReview ª 2017 John Wiley & Sons Ltd…”
mentioning
confidence: 99%
“…15 Although a homozygous, 256C.T nonsense mutation in HAX1 (HAX1 R86X ) has been modeled previously using iPSCs, 16 this variant has been described in only 2 patients and lies outside of exon 2a, the region where the majority of the reported mutations reside. 4 Moreover, this variant has been linked to neurological deficits. 4,17 In addition, viralbased overexpression of wild-type (WT) HAX1 complementary DNA (cDNA) was applied to revert the granulocytic differentiation arrest compared with iPSCs derived from a healthy individual.…”
Section: /2mentioning
confidence: 99%
“…4 Moreover, this variant has been linked to neurological deficits. 4,17 In addition, viralbased overexpression of wild-type (WT) HAX1 complementary DNA (cDNA) was applied to revert the granulocytic differentiation arrest compared with iPSCs derived from a healthy individual. 16 Here, we investigated iPSC-derived granulopoiesis from Kostmann patients (HAX1 W44X -iPSCs) and gene-corrected isogenic lines generated by CRISPR-Cas9 gene editing.…”
Section: /2mentioning
confidence: 99%
“…If the cause of neutropenia is HAX gene mutation, neurological problems are present in 30% of the cases (epileptic seizures, learning difficulty, developmental disorder) (15,16 Tests to be ordered in neutropenic patients: one should not hurry to order tests for neutropenic patients. The clinical picture should always be directive for investigations.…”
Section: Neutrophil Reserve In the Vascular Wallmentioning
confidence: 99%